PELAKSANAAN KEGIATAN PASTORAL CARE DI RUMAH SAKIT PANTI WALUYA SAWAHAN MALANG - Yogina Maria Saapan; Yohanes Emanuel Bisu; Emmeria Tarihoran (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2022)
The experience of pain is a frightening experience for humans. Because many views sick people are synonymous with the punishment of sin. That is why people struggle in various ways to avoid getting sick. Freedom and healing are the deepest longings for humans. People who are sick both mentally and physically need special services and companions. Everyone is called to take part in service to others. Thus the sick can experience complete healing, both medically and specifically through the care of others. To overcome the problems above, the authors use qualitative research methods. The type of research used by the researcher is phenomenological research, the phenomenological approach relates to the implementation of how daily pastoral care officers at Panti Waluya Hospital Malang in carrying out pastoral care activities. Based on the results of the study, the authors obtained the answer that the implementation of Pastoral care Activities at Panti Waluya Sawahan Hospital in Malang was good in carrying out pastoral care activities